A Programmer$1 (Bs Guide to C# 5.0s - Gunnerson, Eric.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
A Programmer$1 (Bs Guide to C# 5.0 is a book for software developers who want to truly understand C#. Whether you$1 (Bve worked with C# before or with another general-purpose programming language, each fast-paced, focused chapter will take you straight to the heart of a feature of C# and show you why it works the way it does. Written by one-time C# Test Lead, Program Manager, and member of the original C# language design team, this book is an ideal companion to the C# Language Specification, and works both as a tutorial and as a reference guide. Now in its fourth edition, you will find up-to-date coverage of all the latest C# features, including Linq, covariance and contravariance, and async support. You$1 (Bll learn how to: Use C# features effectively, in the way they were intended Apply the newest C# features to your coding problems Streamline your database code using LINQ Use async support and the task parallel library to improve performance. Program more efficiently, effectively, and with real insight into this mature and exciting language, with A Programmer$1 (Bs Guide to C# 5.0.s
Keywords: Computer science; Computer Science; Computer Science, general